Nanoparticle-based radiosensitization strategies for improving radiation therapy - Shen, Hongxin; Huang, Hong; Jiang, Zhimei (Frontiers in Pharmacology, 2023)
Radiotherapy remains a major treatment modality for various types of cancer. However, the therapeutic efficiency of radiation is significantly limited by several aspects, including high radiation resistance caused by low reactive oxygen species concentrations and low absorption rate of radiation by tumor tissue, inappropriate tumor cell cycle and tumor cell apoptotic, and serious radiation damage to normal cells. In recent years, nanoparticles have been widely employed as radiosensitizers due to its unique physicochemical properties and multifunctionalities for potentially enhancing the radiation therapy efficacy. Herein, we systematically reviewed several nanoparticle-based radiosensitization strategies for radiation therapy use, including designing nanoparticles that remodel tumor microenvironment, designing nanoparticles that enhance radiation dose deposit, designing chemical drug loaded nanoparticles for enhancing cancer cell sensitivity to radiation, and designing antisense oligonucleotide genetic loaded nanoparticles. The current challenges and opportunities for nanoparticle-based radiosensitizers are also discussed.